(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Interactive methodologies in speech-language pathology represent a paradigmatic shift that has transformed therapeutic intervention for communication disorders. This analysis examines digital technologies, gamification strategies, and multimedia resources in speech and language impairment remediation, demonstrating superior efficacy across diverse populations and clinical contexts through evidence-based research.